The cause is mankind; a liberal program for modern America - Humphrey, Hubert H. 1911-1978. (New York, Praeger, 1964)
The author discusses his liberal political philosophy, with guidelines and proposals for specific solutions to national problems in the areas of human rights, education, culture, health, foreign policy, and national security.
Rashid
Keywords: United States -- Politics and government -- 20th century; United States -- Social policy; United States -- Relations; United States -- Politics and government -- 20th century; United States -- Social policy; United States -- Relations